An experiment in organisation for innovation. (1st January 1998) - Handyside, Tim; Light, Janice
Within the New Technology Group of Courtaulds Coatings, an organisation was designed to address high-value product innovation for a number of different business units. The driver for this experiment was increased pressure to deliver "winning" new technologies and products faster and to obtain maximum leverage from a small research group. Conflicting demands from the businesses within the division had previously led to fragmentation of effort and lack of focus on "high-value" areas. The response in 1992 was to reverse this trend by focusing on a few projects, each with multi-disciplinary input, and with high potential impact in the market. Simultaneously the organisation was developed to reinforce and support this new culture. A traditional discipline-based hierarchical structure was replaced with one reflecting the business drivers specifically through customer focus, commercial awareness, leverage of IT and, above all, flexibility. Four new key roles were created: (1) project managers — delivering results, (2) business market managers — each liaising with a business, (3) technology champions — focusing on critical technology and capability, (4) people manager — responsible for facilitating people development and performance. Information technology is an enabler rather than a threat for the New Technology Group. It supports effective project management, allows technology champions to access new information sources readily, and stimulates the free transfer of information across locations, within and between teams, and across businesses. This is discussed further in the paper, as we describe how the organisation works in practice, and the performance management approach which supports and facilitates it.